Agenda, Alternatives, and Pension in the Old Chilean Democracy: Nineteenth Century Until 1970s [Agenda, Alternativas y Pensiones en la Vieja Democracia Chilena: Siglo Xix Hasta la Década de 1970 - Olavarria-Gambi, M (Universidad de Concepcion, 2021)
Making to converge the historical analysis and that of the politics of public policy, this article examines the trajectory of the Chilean pension scheme from the 19th century to the 1970s. The work focuses on the formulation process of the pension policy – both the highly significant that gained approval as well as those that failed in it –, with the purpose of identifying the characteristics of the policy formulation process of the old Chilean democracy and the role played by actors of the political system in it. Information comes from public archives, press, academic literature, and interviews to key actors. The article concludes that the policy formulation process of the old Chilean democracy was elitist – where the President was the protagonist –, with a high technocratic incidence and with a distribution of competence between the executive and legislative branches that favored the creation and development of the pension scheme. However, this also favored that the pension scheme was oriented to the satisfaction of interests, which later prevented reforms that sought to provide a greater rationality to the State activity and achieve higher levels of equity and integrality in this area. © 2021, Universidad de Concepcion. All rights reserved.